Effect of planting geometry and NPK levels with phosphorus solubilising bacteria on growth and yield of wheat (Triticum aestivum L.) - Satybhan Singh; Virendra Singh; Ankit Singh (Annals of Agricultural Research, 2022)
A field experiment was conducted with wheat cultivar "CBW 38" in three different planting geometry viz. single row planting (SRP), double row planting (DRP) and triple row planting (TRP) in main plots and six nutrient levels with and without PSB in sub plots, tested in split plot design with three replications.The results revealed that different planting geometry and NPK levels with and without PSB significantly affected the different growth and yield attributes significantly. Maximum tillers (5.26 and 7.00 plant–1), dry matter accumulation (45.58 g and 59.00 g), LAI (4.04 and 4.55), spike length (8.76 and 9.43 cm), test weight (47.93 and 49.37 g), grain yield (3.53 and 3.98 t ha–1), were recorded in triple row planting (TRP) and 125% RDF + PSB, respectively. The maximum economic advantage (net returns and B:C ratio) (` 50,435/- and 1.93) was also recorded in TRP + 125% NPK + PSB.